2011
DOI: 10.1007/s00723-011-0277-6
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Catalytic Center of TiO2/SO4 2− Solid Superacid Catalyst by X-Band In Situ High-Temperature EPR Spectroscopy

Abstract: Paramagnetic centers of the solid superacid catalyst in the sulfated TiO 2 are prone to the electron paramagnetic resonance (EPR) spectroscopy. The induction of the catalytic-active sites in TiO 2 powder presubmerged in H 2 SO 4 solution as a function of the calcinated temperature of 293-873 K is investigated by X-band in situ continuous-wave EPR measurements. Sulfated-acid sites composed of the Ti 3? ion are formed upon calcination. The overall experimental results show that the population of these sites goes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…After calcination at 600 °C and 650 °C, the crystal structures of the catalysts were completely anatase, without any rutile type. Zhang et al 26 and Zhu et al 27 showed that TiO 2 could be transformed into rutile at 600 °C without SO 4 2− . The presence of SO 4 2− will prevent this polymorphic transformation, resulting in the preservation of the anatase phase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After calcination at 600 °C and 650 °C, the crystal structures of the catalysts were completely anatase, without any rutile type. Zhang et al 26 and Zhu et al 27 showed that TiO 2 could be transformed into rutile at 600 °C without SO 4 2− . The presence of SO 4 2− will prevent this polymorphic transformation, resulting in the preservation of the anatase phase.…”
Section: Resultsmentioning
confidence: 99%
“…After calcination at 600 1C and 650 1C, the crystal structures of the catalysts were completely anatase, without any rutile type. Zhang et al 26 and Zhu et al 27 showed that TiO 2 could be transformed into rutile at 600 1C without SO 4…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…Nevertheless, most of the studies use ex situ EPR detection, which provides information on stable free radicals at the beginning and end of reactions. , Since the free radical reaction is a continuous process, the information during the reaction process could only be inferred from the initial and the final results. , The in situ EPR detection could observe the evolution of stable free radicals in real-time, reflecting the reaction process directly. In some studies of catalytic conversion of organic fuel, in situ EPR is used to measure the free radicals generated from covalent bond rupture, which has become a powerful characterization for the analysis of reaction mechanisms. In situ EPR detection provides a new idea for studying the coke formation mechanism of bio-oil. However, limited studies use in situ EPR to study the coke formation mechanism of bio-oil, and knowledge about stable free radicals during bio-oil pyrolysis is scarce.…”
Section: Introductionmentioning
confidence: 99%